2007
DOI: 10.2215/cjn.01920507
|View full text |Cite
|
Sign up to set email alerts
|

Increased Occurrence of Pericardial Effusion in Patients with Autosomal Dominant Polycystic Kidney Disease

Abstract: Background and objectives: Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary disease with prominent connective tissue manifestations. A frequent occurrence of asymptomatic pericardial effusion has been observed in patients with ADPKD.Design, setting, participants, & measurements: Consecutive computed tomography scans from 60 patients with ADPKD (group 1), 100 patients without ADPKD and with serum creatinine concentration of >1.1 mg/dl (group 2), and 100 potential kidney donors (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…We found that 45.7% subjects (54 of 118) had pericardial effusions comparable to the 35% prevalence previously reported (64). There was no significant association between renal function, cardiac abnormalities or pericardial effusion and bronchiectasis.…”
Section: Radiographic Bronchiectasis In Adpkdsupporting
confidence: 90%
“…We found that 45.7% subjects (54 of 118) had pericardial effusions comparable to the 35% prevalence previously reported (64). There was no significant association between renal function, cardiac abnormalities or pericardial effusion and bronchiectasis.…”
Section: Radiographic Bronchiectasis In Adpkdsupporting
confidence: 90%
“…22,35 Patients with ADPKD also exhibit prominent connective tissue abnormalities, 38 including abnormal arterial remodeling, intracranial aneurysms, hernia/diverticula, and dilation of the pericardium with pericardial effusion. 39 Recent studies 40,41 also show an approximately threefold increase in the occurrence of bronchiectasis in patients with ADPKD. Moreover, the bronchiectasis is frequently coupled with irregular bronchial wall thickness, without evidence of recurrent airway infection, inferring airway wall defects and possible ASM involvement.…”
Section: Discussionmentioning
confidence: 97%
“…for understanding the fibrotic defects that are often associated with PKD (Cuppage et al, 1980;Wilson et al, 1992), as well as understanding other Pkd1 matrix-associated phenotypes, including intracranial aneurysm (Brooke et al, 2003;Ruigrok et al, 2005); vascular fragility and maintenance of the aortic wall ECM (Kim et al, 2000;Hassane et al, 2007); overlapping connective tissue disorders (Somlo et al, 1993;Kaplan et al, 1997); abdominal wall hernia (Morris-Stiff et al, 1997); and increased pericardial compliance associated with pericardial effusion in ADPKD patients (Qian et al, 2007). Our finding that a reduction in matrix gene expression by col2a1 knockdown can rescue polycystin axis curvature defects suggests that abnormalities in matrix composition or integrity are likely to be developmental defects linked directly to polycystin function, as opposed to secondary consequences of tissue damage or deformity.…”
Section: Research Articlementioning
confidence: 99%
“…Vascular defects are also observed in Pkd1 hypomorphic mouse mutants (Kim et al, 2000;Hassane et al, 2007), where basement membrane thickening is the earliest pathology associated with dissecting aneurysm (Hassane et al, 2007). Other extra renal manifestations of ADPKD that may involve matrix structural defects include gastrointestinal cysts, cardiac valvular defects and pericardial effusion (Hossack et al, 1988;Qian et al, 2007). An altered ECM has long been known to be associated with ADPKD pathology in human tissue (Candiano et al, 1992;Somlo et al, 1993), and in ADPKD animal and cell culture models (Schafer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%